Europa Środkowo-Wschodnia w historycznych i politologicznych koncepcjach Aleksieja Millera - SZABACIUK, Andrzej (Historia i Świat, 2012)
The following paper briefly presents the views of Alexey I. Miller, an incredibly popular in the West Russian researcher, on the phenomenon of Central-Eastern Europe; both in political and historical context. His somewhat original perspective affects significantly his outlook on „historical policy” of Central-European states. Need we mention that a specific strive for monopoly to present this area’s history in a particular way influences relations between Russia and the former eastern block countries to a great extent.